Sex begets violence mating motives, social dominance, and physical aggression in men. [article]. - Ainsworth, Sarah E.
There are sizable gender differences in aggressive behavior, with men displaying a much higher propensity for violence than women. Evolutionary theories suggest that men's more violent nature derives in part from their historically greater need to compete over access to potential mates. The current research investigates this link between mating and male violence and provides rigorous experimental evidence that mating motives cause men to behave violently toward other men. In these studies, men and women were primed with a mating motive and then performed a nose-blast aggression task. Being primed with mating led men, but not women, to deliver more painful blasts of white noise to a same-sex partner (but not an opposite-sex partner). This effects was particularly pronounced among men with an unrestricted sociosexual orientation, for whom competition with their partner (and thus had achieved dominance through non aggressive means), the effect of the mating prime on aggression was eliminated. These findings provide insight into the motivational roots of male aggression and illustrate the value of testing theories from evolutionary biology with rigorous experimental methods. - (from the authors)
Keywords: Maner, Jon K; Aggression; Mating; Motivation; Evolutionary psychology